Optimized Eleutherine bulbosa Urb. bulb extract on the Inhibition of 3D retinoblastoma spheroids cultured in type I murine collagen - Ammar Akram Kamarudin; Nor Hafiza Sayuti; Mohamad Zulhafiz Shafiq Zulhilmi Cheng; Norazalina Saad; Nur Hanisah Azmi; Norhaizan Mohd. Esa (National library of medicine, 2025)
● AIM: To investigate the efficacy of Eleutherine bulbosa (Mill.) Urb. bulb extract (EBE) on the 3D human retinoblastoma cancer cells (WERI-Rb-1) spheroids and explore its apoptotic mechanism. ● METHODS: The 3D WERI-Rb-1 and human retinal pigmented epithelium cells (ARPE-19) spheroids were developed using type 1 murine collagen that was excised from the rat tail tendon and cultured via hanging drop and embedded techniques. The cytotoxic activity was examined by Alamar blue assay meanwhile, the morphological characteristics were assessed by 4’,6-diamidino-2phenylindole (DAPI) and scanning electron microscopy (SEM). The mRNA and protein expressions of apoptotic and antioxidant signal transduction pathways were explored to ascertain its molecular mechanisms. The statistical analysis was carried out using GraphPad Prism. ● RESULTS: The Alamar blue assay portrayed higher half maximal inhibitory concentration (IC50 ) values of EBE and cisplatin on 3D WERI-Rb-1 model as compared to the previous study on 2D model. The results of DAPI and SEM illustrated apoptotic features upon treatment with EBE and cisplatin in a dose-dependent manner on 3D WERIRb-1 model. The mRNA and protein levels of apoptotic and antioxidant-related pathways were significantly affected by EBE and cisplatin, respectively (P<0.05). The regulation of gene and protein expressions of 3D WERI-Rb-1 spheroids differed from the 2D study, suggesting that the tumor microenvironment of extracellular matrix (ECM) collagen matrix hindered the EBE treatment efficacy, leading to apoptotic evasion. ● CONCLUSION: A significant inhibition effect of EBE is observed on the 3D WERI-Rb-1 spheroids. The presence of ECM causes an increase in cytotoxic resistance upon treatment with EBE and cisplatin.